Comparative evaluation of colonoscopy, fecal immunochemical test, and a novel risk-adapted approach for colorectal cancer screening: preliminary baseline results of a multicentre randomised controlled trial (Target-C). Issue 1 (October 2019) - Chen, Hongda; Li, Ni; Lu, Ming; Shi, Jufang; Ren, Jiansong; Liu, Chengcheng; Zhang, Yueming; Jiang, Zheng; Zhang, Zhihui; Dai, Min
Abstract: Background: For colorectal cancer (CRC) screening, the use of risk prediction models to identify potential high-risk populations and implementation of appropriate risk-adapted screening may be more cost-effective than traditional screening strategies. However, evidence from randomised controlled trials is lacking. This study aimed to evaluate colonoscopy, fecal immunochemical test (FIT) and a novel risk-adapted screening approach in a large-scale multicentre randomised controlled trial in China. Methods: This ongoing trial has been conducted in six study centres in five provinces in China since May 2018. People aged 50–74 years living in the study areas were approached to assess eligibility. Overall, 19 582 eligible participants were enrolled from May, 2018, to May, 2019. After providing signed informed consent, participants were randomly assigned to one of three screening groups, with a 1:2:2 ratio: (1) one-time colonoscopy (n=3937); (2) annual fecal immunochemical test (FIT; n=7858); and (3) annual risk-adapted screening strategy (n=7787). The risk-adapted screening strategy used an established CRC risk scoring system, the Asia-Pacific Colorectal Screening Score. Participants at high risk of CRC were referred for colonoscopy, whereas participants at low risk of CRC were referred for a FIT. Participants with positive FIT results were also referred for diagnostic colonoscopy. Information on clinical reports and epidemiological risk factors were collected and stored in a web-based data system. The primary outcome was detection rate of advanced colorectal neoplasia and secondary outcomes included rate of adherence to the study protocol, compliance rate of colonoscopy, detection rate of any neoplasm, complication rate, and the rate of mortality. A 4-year screening phase (with 1-year baseline screening and 3 years of follow-up screening) will be conducted for all participants and a subsequent 6-year active and passive follow-up phase will be implemented. Here we present the preliminary baseline screening results. This study was approved by the Ethics Committee of the National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College (18-013/1615) and the protocol was registered in the Chinese Clinical Trial Registry (identifier: ChiCTR1800015506). Findings: After we excluded 36 participants who did not meet the inclusion criteria after further evaluation, 19 546 participants were included for the primary analysis (3916 colonoscopy, 7854 FIT, and 7776 risk-adapted screening). Mean age was 60·5 (SD 6·5) years and 41·7% (8154 of 19 546) were men. No statistically significant differences for age and sex distribution were observed between the groups. Participation rates were 42·5% (1665 of 3916) for colonoscopy, 94·0% (7386 of 7854) for FIT, and 85·2% (6628 of 7776) for risk-adapted screening. Of the participants assessed to be at high risk of CRC in the risk-adapted group (18·9%, 1472 of 7776), 49·2% (724 of 1472) accepted colonoscopy screening, a significantly higher proportion than in the colonoscopy group (42·5%; p<0·05). Of participants assessed to be at low risk of CRC in the risk-adapted screening group (80·7%, 6279 of 7776), 94·0% (5904 of 6279) accepted FIT screening, similar to the rate in the FIT group (94·0%). The overall positivity rate of FIT was 14·3%, and over 85% of participants with positive FIT results undertook subsequent diagnostic colonoscopy. For the intention-to-screen analysis, detection rates for advanced colorectal neoplasms were 2·93% for colonoscopy, 1·29% for FIT and 1·83% for risk-adapted screening. The FIT and the risk-adapted screening groups had lower numbers of colonoscopies needed to detect one advanced neoplasm than the colonoscopy group (eight, ten, and 15 colonoscopies, respectively). Interpretation: This is the first large-scale population-based trial in China to compare effectiveness of three different colorectal cancer screening strategies targeting adults aged 50–74 years. For the interim analysis of the baseline screening in this trial, the FIT and the novel risk-adapted screening approach had higher participation rates than the colonoscopy screening approach, and they required fewer numbers of colonoscopies to detect one advanced neoplasm, indicating the feasibility and effectiveness of these two approaches in population-based CRC screening. The findings of this study may provide timely evidence in designing effective population-based CRC screening strategies. Funding: This study was sponsored by Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences (2017-I2M-1-006) and the National Natural Science Foundation of China (81703309).